2006
DOI: 10.2113/gsjfr.36.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Modern Distribution of Benthic Foraminifera From Disko Bugt, West Greenland

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 55 publications
(54 reference statements)
1
87
0
Order By: Relevance
“…2), the δ 18 O c record shows only minor variability (0.3 ‰). The amplitude difference between the measured δ 18 O c and reconstructed BWT TF indicates that a benthic foraminiferal fauna is not only affected by temperature and salinity but also nutrient availability exerts an influence via marked changes in the so-called "food indicator species" (e.g., N. labradorica, Islandiella spp., M. barleeanus; Hald and Korsun, 1997;Polyak et al, 2002;Lloyd, 2006;Ivanova et al, 2008). Thus, the large temperature variations in the BWT TF are most likely an overestimation due to the training set, and we must conclude that the training set and transfer functions used in the present study are not able to capture the small temperature variations as suggested by our δ 18 O c values.…”
Section: Mid-holocene (9800-1500 Yr Bp)mentioning
confidence: 76%
See 2 more Smart Citations
“…2), the δ 18 O c record shows only minor variability (0.3 ‰). The amplitude difference between the measured δ 18 O c and reconstructed BWT TF indicates that a benthic foraminiferal fauna is not only affected by temperature and salinity but also nutrient availability exerts an influence via marked changes in the so-called "food indicator species" (e.g., N. labradorica, Islandiella spp., M. barleeanus; Hald and Korsun, 1997;Polyak et al, 2002;Lloyd, 2006;Ivanova et al, 2008). Thus, the large temperature variations in the BWT TF are most likely an overestimation due to the training set, and we must conclude that the training set and transfer functions used in the present study are not able to capture the small temperature variations as suggested by our δ 18 O c values.…”
Section: Mid-holocene (9800-1500 Yr Bp)mentioning
confidence: 76%
“…4). Both of these species are associated with high-productivity environments (Hald and Steinsund, 1996;Polyak et al, 2002), and N. labradorica is controlled more by food supply than by water temperature (Hald and Korsun, 1997;Lloyd, 2006;Ivanova et al, 2008). Further, the δ 18 O c values during the cold interval only show an increase of 0.15 ‰ (Fig.…”
Section: Early Holocene (11 500-9800 Yr Bp)mentioning
confidence: 95%
See 1 more Smart Citation
“…These groupings are based on the modern distribution of foraminifera in Disko Bugt (Lloyd, 2006a) and also other ecological studies from the Arctic (e.g. Vilks 1964Vilks , 1981Mudie et al 1984;Madsen & Knudsen 1994;Hald & Steinsund 1992;Jennings & Helgadottir 1994;Seidenkrantz, 1995;Hald & Korsun 1997;Korsun & Hald 1998 Disko Bugt has been shown to be linked to high levels of organic material, but this is also associated with strong influx of WGC waters (Lloyd, 2006a) hence their grouping in the Atlantic water group. The Polar Water group includes species commonly found in areas with no Atlantic water influence dominated by colder less saline waters and includes: Cuneata arctica, Spiroplectammina biformis (agglutinated taxa), Cassidulina reniforme and Elphidium excavatum f.…”
Section: B Foraminiferal Analysismentioning
confidence: 95%
“…However, this scatter is most likely an artefact of the decline of number of data points 398 with depth. Upper waters are generally warm (2-4 o C) due to solar heating, but the incursion of 399 Polar Water (Lloyd, 2006a)) at depths between 50m and 300m reduces the temperature between 400 these levels to between 0 and 2 o C. The warm, saline deep water body below 300-500m depth in 401 west Greenland is due to the northward movement of the West Greenland Current. 402…”
mentioning
confidence: 99%